Homer 1 - a new player linking the hypothalamic-pituitary-adrenal axis activity to depression and anxiety - Grinevich, Valéry (Endocrine regulations, 2012)
Homer 1 gene products are involved in the regulation of synaptic transmission and plasticity. Beside other deficits, the Homer 1 knockout (KO) mice show distinct behavioural abnormalities, such as anxiety and depression-like behaviours. In addition, we recently reported that the global deletion of the Homer 1 proteins in mice leads to a conspicuous endocrine phenotype linked to hypertrophy of the adrenal cortex, elevated basal and/or adrenocorticotropic hormone-induced corticosterone and aldosterone release in vitro and in vivo, as well as a drastic increase in the adrenocorticotropic hormone receptor mRNA in the adrenocortical cells. Interestingly, the basal secretion of adrenocorticotropic hormone was not changed in these mutants, which is in line with our recent observations, suggesting that the central limb of the hypothalamic-pituitary-adrenal axis (namely hypothalamic corticotropin-releasing hormone levels and the activation of its neurons in response to restraint stress) is not affected in the Homer 1 KO mice. On the contrary, the elevation of both plasma and intra-adrenal corticosterone and aldosterone concentrations in these mutants clearly indicates that the alteration primarily occurred in the adrenal cortex. We propose that excessive steroid release may contribute to depression- and anxiety-like behaviours and that the Homer 1 gene products may be involved in the pathogenesis of these stress-related mood disorders.